China : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1997)
This paper describes economic developments in the People's Republic of China during 1996-97. In 1996, the authorities succeeded in stabilizing growth at a high level while alleviating the inflation pressures that had characterized the 1993-94 boom. From an average rate of more than 13 percent in 1992-94, real GDP growth eased to 10.5 percent in 1995 and further to 9.7 percent in 1996, reflecting moderation in the aggregate demand components, notably fixed investment. The sectoral real GDP growth pattern in 1996 was broadly unchanged from the first half of the decade.